Prendre en compte l’adoption technologique dès le stade de la conception : le cas d’un projet en viticultureadoption des technologies, conseil agricole, intervention ergonomique en conception, représentation, viticulture - Jean Larbaigt; Céline Lemercier; Irène Gaillard (Perspectives Interdisciplinaires sur le Travail et la Santé)
Viticultural practices must evolve if they are to meet economic, environmental, and sanitary challenges. The agricultural advisory service, enhanced by new technologies, is a promising lever. However, not many farmers are adopting these technologies. The adoption of new technology begins in the design phase where differences in the designers’ socio-cognitive conceptions of the user activity can occur. These gaps can lead to technologies which do not match the future users’ activity needs and, consequently, are often rejected. To reduce these gaps, the input of an ergonomics intervention, which examined a technology design project, was studied through an ongoing description of the ergonomic process. The research led to an objective portrait of the agricultural advisor’s activity, which formed the basis for the cognitive synchronisation of the designers’ work. By carrying out, right from the design stage, socio-cognitive adjustments to the various representations of the user activity, an ergonomics intervention can make it easier for new technology to be adopted.